GENERAL UNDERSTANDING OF MEMORY LOSS AND MEMORY FUNCTION IN THE ELDERLY - Turdikulov Kamronbek Muzaffar o’g’li (PEDAGOGS, 2024)
In this article, the subtle aspects of gerontopsychology are scientifically analyzed. Also, the causes of memory loss in old age and memory functions are highlighted.